Modifikasi Pembelajaran Desain Dasar (Nirmana) bagi Program Studi Animasi - Dyah Gayatri Puspitasari; James Darmawan (Humaniora, 2014)
Nirmana (basic design) is a compulsory major for School of Design-Binus University student. Basically, nirmana related with perception of the sight sense (visual) through organizing sensation components which has related pattern or similarity so that becomes one unity that can be appreciated. Nirmana course prepares the student to have sharpness and sensitivity to visual elements that is the core of the disciplines from art and design, along with its branches. In practice, curriculum Nirmana may not necessarily be applied to all courses. On course of study animation, adjustment is needed, and even some modification to achieve the purpose of learning that is based on the vision course of study. This course study of animation has unique characteristics and slightly different content from other courses, where visual is not the only aspect, but inherent with motion, audio and storytelling. This research aims to discuss the formulation of learning strategies for Animation Courses so it can run optimally.